Impact of the statutory concessionary travel scheme on bus travel among older people: a natural experiment from England. Issue 11 (18th November 2020) - Whitley, Elise; Craig, Peter; Popham, Frank
Abstract: In the context of worldwide ageing, increasing numbers of older people are lonely, isolated and excluded, with serious implications for health, and cognitive and physical functioning. Access to good public transport can improve mobility and social participation among older adults, and policies that improve access and promote use, such as concessionary travel schemes, are potentially important in promoting healthy and successful ageing. Concessionary travel schemes for older people are in place in many countries but are under threat following the global financial crisis. Evidence regarding their success in encouraging activity and social participation is generally positive but based largely on qualitative or observational associations and, in particular, is often limited by the lack of appropriate comparison groups. We use changes in the English statutory scheme, in particular the rising eligibility age from 2010 onwards, as a natural experiment to explore its impact on older people's travel. A difference-in-difference-in-difference analysis of National Travel Surveys (2002–2016) compares three age groups differentially affected by eligibility criteria: 50–59 years (consistently ineligible), 60–64 years (decreasing eligibility from 2010) and 65–74 years (consistently eligible). Compared with 50–59-year-olds, bus travel by 60–74-year-olds increased year-on-year from 2002 to 2010 then fell following rises in eligibility age (annual change in weekly bus travel: −2.9 per cent (−4.1%, −1.7%) in 60–74- versus 50–59-year-olds). Results were consistent across gender, occupation and rurality. Our results indicate that access to, specifically, free travel increases bus use and access to services among older people, potentially improving mobility, social participation and health. However, the rising eligibility age in England has led to a reduction in bus travel in older people, including those not directly affected by the change, demonstrating that the positive impact of the concession goes beyond those who are eligible. Future work should explore the cost–benefit trade-off of this and similar schemes worldwide.